2020
DOI: 10.15826/analitika.2020.24.4.003
|View full text |Cite
|
Sign up to set email alerts
|

Sample preparation of soils and bottom sediments for gas chromatography–mass spectrometry determination of PAHS

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a class of compounds which have been known to be carcinogenic, teratogenic and mutagenic as well as act as pollutants of environmental objects. The determination of PAHs in complex matrices is difficult, and it is very important to use an efficient sample pretreatment technique. A sample preparation technique was developed involving extractive freezing-out and centrifugation of the samples for the determination of polycyclic aromatic hydrocarbons (PAHs) in soils and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In this case, the extraction and preconcentration of analytes and the purification of extracts are combined in one stage [85]. Temerdashev et al [86] demonstrated the efficiency of the use of this method in the determination of PAHs in soils and bottom sediments and proposed an extraction mixture with 15% acetonitrile in order to determine 10 light PAHs. In this case, the determination limits of analytes varied from 0.83 to 0.92 μg/kg.…”
Section: Homogeneous Liquid-liquid Extractionmentioning
confidence: 99%
“…In this case, the extraction and preconcentration of analytes and the purification of extracts are combined in one stage [85]. Temerdashev et al [86] demonstrated the efficiency of the use of this method in the determination of PAHs in soils and bottom sediments and proposed an extraction mixture with 15% acetonitrile in order to determine 10 light PAHs. In this case, the determination limits of analytes varied from 0.83 to 0.92 μg/kg.…”
Section: Homogeneous Liquid-liquid Extractionmentioning
confidence: 99%